PELAKSANAAN RESTRUKTURISASI KREDIT PADA MASA PANDEMI COVID-19 PADA BANK RAKYAT INDONESIA UNIT BUKIT BARISAN IMAM MUNANDAR PEKANBARU RIAU. - Fania Hanisa Sundjaya; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The covid-19 pandemic in Indonesia has had many impact. One of them isin the health sector in Indonesia and then in the economic sector in Indonesia.One of the institutions affected by the Covid-19 pandemic is PT. Bank RakyatIndonesia, Tbk. According to it’s use, the bank distributes funds to the public inthe form of credit, the bank provides credit facilities. Although the analysis hasbeen carried out, there is no credit facility without risk. If the bank in providingcredit has seen a non performing loan, the bank must try to save the credit. In thiscase, PT. Bank Rakyat Indonesia, Tbk seeks to be able to relaunch bad loans, sothat the recipient of the credit has the ability to repay both interest and credit. Theimplementation of credit restructuring in accordance with POJK number11/POJK.03/2020 can be given to debtors affected by the spread of Covid-19,including UMKM debtors.This research is uses empirical sociological research methods, becausethe author directly conducts research at the research site to provide a completeand clear picture of the problem under study. This research was conducted in PT.Bank Rakyat Indonesia, Tbk Unit Bukit Barisan Imam Munandar PekanbaruRiau, while the population and sample are all parties, namely the bank Mr. AdiSaputra, the OJK as the policy maker, one of them Mr. Yamin, and the customer isMr. Handoko. The data sources used are primary data, secondary data, andtertiary data. The data collection techniques in this study was structuredinterviews in the form of directly with the parties involved in the implementationof credit restructuring during the Covid-19 pandemic.The result of this study there are several things that can be concluded.First, the implementation of credit restructuring during the Covid-19 pandemic atPT. Bank Rakyat Indonesia, Tbk was carried out with a type of term extension,namely interest payments only and delays in principal receivables. Second,obstacles in the implementation of credit restructuring, namely in the negotiationprocess where customers are not cooperative and the bank’s movement is limitedin conducting customer checking processes.Keywords : Credit restructuring, Pandemic period